The Effectiveness of Learning Management System in Higher Education: A Case Study of Social Sciences Course Content - Yenni Arnas; Andy Ahmad; Fajarianto, Otto (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
Due to the Ministry of Education and Culture's circular letter, the education sector must innovate in carrying out its duties and functions in educating students even though they do not meet face-to-face. The modern education paradigm requires educators and students to be technologically literate. The online learning that is intended is based on ICT by utilising the internet as the main media. Learning Management System is a software for administration, documentation, reports of an activity, teaching and online learning activities online. Social Science is a subject in schools that is designed on the basis of phenomena, problems, and social realities with an interdisciplinary approach. The utilisation of Learning Management System in social studies learning concept courses became the study of this research. The data collection used is a questionnaire given to students through Google Form at the final meeting of the lecture. This research uses non-test data collection techniques in the form of observation, questionnaires, and documentation. In this Learning Management System, the learning system and communication between lecturers and students can be carried out well by utilising the features available in the LMS application.